Helicobacter pylori infection and dental care. Issue 1 (July 1995) - Hardo, P G; Tugnait, A; Hassan, F; Lynch, D A; West, A P; Mapstone, N P; Quirke, P; Chalmers, D M; Kowolik, M J; Axon, A T
Abstract : Sixty two patients (mean age 45.6 years) were assessed for oral hygiene and periodontal disease by dental examination before endoscopy. Information about oral care, smoking, and dentures was obtained and samples of dental plaque collected. The presence of Helicobacter pylori in plaque as sought by culture and polymerase chain reaction (PCR), and gastric antral biopsy specimens were taken for histological examination. Although H pylori was detected in the antral specimens of 34 patients (54%) all of the cultures of dental plaque were negative, and PCR was only positive from the dentures of one patient. Smokers had poor oral hygiene, visited their dentist less often, and brushed their teeth less frequently. There was no correlation of H pylori gastritis with either dental hygiene or periodontal disease. These results suggest that dental plaque or dentures are not an important reservoir for H pylori and are probably not a significant factor in transmission of the organism. The conflicting results in published works may be caused by differences in sample collection, culture techniques, or oral contamination from gastric juice as a result of gastro-oesophageal reflux at the time of endoscopy.